Pengaruh Good Corporate Governance dan Kebijakan Dividen Terhadap Nilai Perusahaan - Leonardo Leonardo; Sekar Mayangsari (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
The purpose of this research is to examine the impact of good corporate governance and dividend policy on firm value. This research used the sample of consumer goods industry subsector companies which listed in Indonesian Stock Exchange during 2020-2022. The number of companies sampled in this study were 49 companies. Hypothesis in this research are tested by multiple linear regression analytical. Data analysis show that institutional ownership and independent commissioner has positive effect firm value because through the establishment of good corporate governance a company can add value to investors or shareholders in the company. While, managerial ownership, audit committee, and dividend policy do not have effect on firm value.